Strategi Pemasaran Dan Pelayanan BPR Nusamba Dalam Meningkatkan Nasabah - M. ROSI; Bahrur Rosi; Devi Hardianti Rukmana (CV. ITTC INDONESIA, 2023)
In banking competition, each financial institution must implement neat and clear marketing in order to gain market share. Invitations to win the market between BPR and Commercial Banks are very selective, with the increasing number of other financing institutions and cooperatives. The scheme implemented by BPR Nusamba to gain market share is a very adaptive and competitive interest rate, excellent service, effective, efficient and profitable. Sustainable promotion and direct involvement in the community. Financing the productive business sectors of trade, industry and agriculture as well as 3P services (fast process, easy requirements and guaranteed security). Currently, people are more careful in choosing an institution or body that is considered capable of facilitating and serving the economy. They really need financial institutions that are good at serving and facilitating them. Apart from that, BPR is present in the community and is the answer to their economic problems. The progress of Rural Bank activities is increasingly rapid and its presence is spread across various geographies, both urban and rural. The public has a lot of empathy for the role and function of BPR, including in funding matters in the form of requests for credit loan assistance. The researcher used the descriptive approach method used in this research by providing a clear picture and description of a problem.